Hospice Use Following Implantable Cardioverter-Defibrillator Implantation in Older Patients: Results From the National Cardiovascular Data Registry. Issue 21 (24th May 2016) - Kramer, Daniel B.; Reynolds, Matthew R.; Normand, Sharon-Lise; Parzynski, Craig S.; Spertus, John A.; Mor, Vincent; Mitchell, Susan L.
Abstract : Background—: Older recipients of implantable cardioverter-defibrillators (ICDs) are at increased risk for short-term mortality in comparison with younger patients. Although hospice use is common among decedents aged >65, its use among older ICD recipients is unknown. Methods and Results—: Medicare patients aged >65 matched to data in the National Cardiovascular Data Registry – ICD Registry from January 1, 2006 to March 31, 2010 were eligible for analysis (N=194 969). The proportion of ICD recipients enrolled in hospice, cumulative incidence of hospice admission, and factors associated with time to hospice enrollment were evaluated. Five years after device implantation, 50.9% of patients were either deceased or in hospice. Among decedents, 36.8% received hospice services. The cumulative incidence of hospice enrollment, accounting for the competing risk of death, was 4.7% (95% confidence interval [CI], 4.6%–4.8%) within 1 year and 21.3% (95% CI, 20.7%–21.8%) at 5 years. Factors most strongly associated with shorter time to hospice enrollment were older age (adjusted hazard ratio, 1.77; 95% CI, 1.73–1.81), class IV heart failure (versus class I; adjusted hazard ratio, 1.79; 95% CI, 1.66–1.94); ejection fraction <20 (adjusted hazard ratio, 1.57; 95% CI, 1.48–1.67), and greater hospice use among decedents in the patients' health referral region. Conclusions—: More than one-third of older patients dying with ICDs receive hospice care. Five years after implantation, half of older ICD recipients are either dead or in hospice. Hospice providers should be prepared for ICD patients, whose clinical trajectories and broader palliative care needs require greater focus.